Teachers’ Teaching Capability in Urban and Rural Areas: A Comparative Study - Kusin, Sittie Maguid (Future Science / FSH-PH Publications, 2022)
In order to achieve excellence in teaching and learning, it needs stronger, skillful teachers with technical expertise. The study was conducted to compare the teaching capability of teachers in Urban and Rural areas. The study utilized descriptive-comparative and mixed methods of research, and it was conducted at selected schools in the urban Cotabato City division and schools in the rural, Maguindanao-1 division. There were 56 totals of teachers, both in urban and rural areas. Respondents determined using total complete enumeration from 1 to 6 English teachers and the principal of each school. A self-made survey questionnaire was used to gather data. Random interviews and observations were done to validate respondents' answers. Statistical tools used were mean to describe teaching capability and a T-test of independent means to determine the difference. The extent of teaching capability of teachers in urban areas in terms of teachers' teaching strategies was rated very satisfactory, and in the rural area rated satisfactory. Implementing classroom management in urban areas was very satisfactory, while rural ones rated satisfactory. The difference between teachers' teaching capability in urban and rural areas was not significant. It is concluded that teachers in both urban and rural areas were performing well, although there is little difference in the implementation of the task as their teaching capabilities. This recommends that teachers in urban and rural areas improve their teaching capabilities and give more effort to mold their pupils to become competent to face the standards at the next level of their education